What are business models? - Baden-Fuller, Charles (Henry Stewart Talks, 2013)
The business model agenda, Customer search systems – Project vs. scale based customer engagement, The three core choices for value delivery, Monetize and complementors Business models define competition, Innovation of the business model, Hybridization of business models, Business models and cognition, Management agenda
Reviewed at 2020/09/30